Psychological Capital, Authentic Leadership, Job Satisfaction And Job Performance - Kusnadi Kusnadi; Abdul Haeba Ramli (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The purpose of this study was to explore the relationship between authentic leadership, psychological capital, job satisfaction and job performance in employees working in manufacturing companies in the province of Banten, Indonesia. This study was conducted with 387 respondents. The research respondents were selected using the purposive sampling method. The research conducted was a quantitative study using the Structural Equation Model (SEM) method. The results of this study prove that there is an influence between psychological capital on job satisfaction, and authentic leadership on job satisfaction; Then job satisfaction affects work engagement and work engagement affects job performance. The managerial implications of this study are that companies must be able to encourage employees to have good work performance by paying attention to variables that can improve it, namely employees must feel full involvement between themselves and the organization, then employees must also be happy with their work and then employees must be confident in what they do. Keywords - Authentic Leadership, Psychological Capital, Job Satisfaction, Work Engagement, Job Performance